Los valores éticos y cristianos para la transformación del contexto sociocultural de los estudiantes del primer año de la “Unidad Educativa Privada San Vicente, el Paraíso, Caracas” (2015)
This paper deals with the investigation of the Venezuelan socio-cultural reality expressed specifically in a community of the capital, located in the southwest area of the city known as the "Brisas del Paraiso" sector. The main objective of the study is to confirm the possibility of achieving the transformation of this reality through education in ethical values and Christian students. To accomplish this goal, a group of students of 1st year Bachelor of Education Unit Private "San Vicente", located in the area before indicated selected. The choice of both the type of institution and the age group studied was not done randomly, but associated with a predominantly investigative purpose: to analyze to what extent an educational program is efficient to achieve noticeable changes in the behavior of young people, and enable them to confront and transform the harsh reality. Towards this end the objectives and action plan of the thesis (Problem Statement, Reference Framework, Research Methodology and Pedagogical Proposal) focused. The conclusions allowed: a) find that actually affects the behavior of adolescents, b) that the institution should be involved in the family and social environment of the student to achieve the proposed goals, and c) it is advisable to apply an educational proposal on ethical values and Christians in any educational institution and extend the study overall.